Savoirs et actions de jardinage - Jean-Baptiste Poinot (Projets de Paysage)
This article reports on the first year of a landscape architect-inhabitant-gardener experiment conducted as part of a project for the rehabilitation of a former housing estate in Mérignac. It describes different methods for rethinking landscape architecture based on the experience of inhabitants and their capacity to participate in landscape planning. The first method involved conducting interviews with the inhabitants in their gardens. Summary transcriptions of these interviews made it possible to define a precise strategy of interventions and planning over time and to identify collective spaces the forms and functionalities of which were not defined beforehand. This method led to a singular notion of landscape action, that of the landscape architect-inhabitant-gardener. The second part of the article describes the ways in which action taken from such a perspective is implemented and demonstrates the benefit of the approach, namely the capacity to take individual experiences into account in the design of collective spaces.